STUDY AND QUANTIFICATION OF THE CAROTENOIDS BY SPECTROSCOPIC METHODS OF THE «NISPERO DE LA SIERRA> AND IT´S VALORATION AS A FUNCTIONAL FOOD - Chasquibol, Nancy (2006)
In this research we studied the fruit of «Níspero de la Sierra>) as functional food. The carotenoids have been fractioned in two bands by layer chromatography. The major pigment was identified by it's spectral caractheristics in several solvents: ¡3-caroteno (15.18 mg/kg). The cuantification of minerals and proximal analysis were: potasium (1566 ppm), sodium (745 ppm), calciumn (424 ppm), magnesio (290 ppm), iron (5.40 ppm); and carbohidrates (34 .72%), respectively.